Penggunaan Laboratorium Virtual dan Google Classroom dalam Penguatan Karakter Religiusitas Siswa Kelas XII IPA MAN Insan Cendekia Kota Palu di Masa PJJ Pandemi Covid-19 - Latief, Riskayati (Biology Teaching and Learning, 2021)
Abstract. This Best Practice research aims to: Describe the Strengthening on Students' Religious Character during the distance learning period by using a Virtual Laboratory and Google Classroom. Research method: descriptive analysis with documentation as the source of research data and questions indicator instrument concerning student’s religious character. Strategies applied was online learning through Virtual Laboratory which presented learning videos and Google Classroom for task upload, through the following stages: (1) Teacher prepared the Lesson; (2) Teacher prepared learning materials and assignments thus uploaded them on Google Classroom; (3). Students upload their tasks through Google Classroom media (4) Teacher monitored the implementation of online learning process; (5) Teacher provided feedbacks on the online learning. Result of research: a significant data was obtained at the level of religious character strengthening, on the concept of growth and development, the average was 88,54% on good category, the concept of Photosynthesis at the average of 92,55 % on very good category. The conclusion of this research is there was strengthening of religious character through the use of virtual laboratory and google classroom.Keywords: covid-19, google classroom, virtual laboratory,strengthening of religious character, online learning.